Grassroots of democracy - Shah, A.M. (ed.) (Delhi, 2007)
Originally conceived by India$1 (Bs most influential modern anthropologist M.N.Srinivas and his eminent colleague A.M.Shah, this book contains nineteen essays based on field studies of two national elections in India$1 (Bs rural, tribal and urban communities, within ten Indian states. It includes an Introduction by A.M. Shah and an Epilogue by the psephologist and political scientist Yogendra Yadav. The studies which comprise the bulk of this book were conducted by sixteen sociologists at the Delhi School of Economics under the direction of M.N. Srinivas and A.M.Shah. Demonstrating the importance of fieldwork for studying elections (as compared to the questionnaire and interview method), this book provides an entirely novel perspective on the study of elections very different from the one usually projected through the interpretation of statistics. This sociologist$1 (Bs micro-view contrasts with the more standard macro-view provided by political scientists, journalists and psephologists. Among the many reasons for the importance of this book as a departure from standard electoral studies is the thoroughgoing manner in which it questions the general assumption of the rational individual as the sole arbiter of his/her voting behaviour. It analyses in detail the role of an array of social factors in electoral processes and also delineates the continuity between local, regional and national politics. In so doing, it reveals how Indian democracy actually operates at the grassroots. This important new work will interest sociologists, anthropologists, political scientists and anyone interested in India$1 (Bs polity and society. With its diverse narratives and jargon-free descriptions of actors in the political arena, this is also a book entirely accessible to non-specialists interested in India$1 (Bs complex political and social processes during the drama-filled times when India goes to the polls.s
Keywords: Democracy